Digital Leisure and Agency of Well-being: Uncertainty in Middle Class Households (2020)
This article describes how a deceptive event framed in the “interview” journalistic genre makes up a deceptive narrative that, even after being rectified, will continue to affect the audiences summoned emotionally and ideologically. It is a case study developed through a content analysis to explain how a fake news appears in a newscast of private television in Colombia, through the introduction of false phrases that, combined with the framing, emotional narratives and the distortions, sharpen the political polarization and reveal how are these emotions inserted in the news narrative. The results show us that the biases of distortion, not necessarily partisan, and the emotions aligned with the ideological principles together with the gains of the market, are the breeding ground for the gestation of false news. The objective of this paper is to show how traditional media, such as television and its strategies of narrative persuasion, provide their audiences, (fake) materials for the (skewed) construction of (fake) news, while exciting the public, which generates political and economic benefits for the news médium the economic group that it is part of, and the presidential candidate supported by the group. The most important finding is that the emotional bias sought by the private media of news information studied is not limited to an explanation of its partisan character; at stake are the audiences of the best schedule of Colombian television, and the economic benefits for a segment of the advertising market.